Gains from Anchoring Inflation Expectations : Evidence from the Taper Tantrum Shock - Bems, Rudolfs (IMF Working Papers; Working Paper ;, 2019)
Many argue that improvements in monetary policy frameworks in emerging market economies over the past few decades, have made them more resilient to external shocks. This paper exploits the May 2013 taper tantrum in the United States to study the reaction of 18 large emerging markets to an external shock, conditioning on their degree of inflation expectations' anchoring. We find that while the tapering announcement negatively affected growth prospects regardless of the level of anchoring, countries with weakly anchored inflation expectations experienced larger exchange rate pass-through to consumer prices, hence comparatively higher inflation. We conclude that efforts to improve the extent of anchoring of inflation expectations in emerging markets pay off, as they ease the trade-off that central banks face when external shocks weaken growth prospects and trigger currency depreciations.